Evolution of Published Research on Molten Slags and Fluxes in the Second Millennium. Issue 7 (7th March 2013) - Boom, Rob; Riaz, Shahid; Xiao, Yanping; Mills, Kenneth C.
Abstract: Starting in 1997 with the 5th International Conference on Slags and Fluxes, a survey on research on slags has been carried out for every conference on slags and fluxes. Trends from 1980, the year of the first conference in Halifax, Canada, have been traced and discussed. For the ninth conference in the series, the survey is focused on research on molten slags and fluxes published from 2000 to 2010. In these 10 years, the center of gravity of the metals industry has shifted eastwards towards China, and the slags and fluxes literature follows this geographical shift with reference to numbers of papers published per annum. The increased attention on sustainable metals production (including recycling of valuable metals and reuse of slags as cement or construction material) is reflected in the type of research on slags. Minimization of slag production per unit of metal produced is another trend triggering innovative production process development. An in‐depth analysis is given of papers published in 2010 in selected journals from China, Europe and USA in terms of slag systems, type of research and geographical origin. Abstract : A survey on research on slags has been carried out published from 2000 to 2010. The centre of gravity of the metals industry has shifted eastwards towards China, and slags and fluxes literature follows this shift. Increased attention on sustainable metals production is reflected in the type of research on slags. An in‐depth analysis is given of papers published in 2010 in selected journals from China, Europe and USA.